Analysis of the online consumption of female university students (Revista de Investigaciones Universidad del Quindío, 2022)
E-commerce has been increasing in recent years, which has represented an alternative used by companies to stimulate their development and growth, but it was undoubtedly the health restrictions issued by governments around the world in 2020, which caused purchase rates to increase on a large scale among consumers, being practically the only way to acquire many brands that even closed their physical points of sale. Hence the need to analyze the changes in consumer habits that allow us to understand and analyze them in order to establish our marketing strategies.The present research is quantitative and exploratory; surveys were applied to a sample of 231 university students. An analysis of the main theories on marketing and consumer behavior is presented, as well as a review of the state of the art on online shopping habits and the confidence to make them. The findings describe the change in purchasing habits after the pandemic, the main reasons why female university students buy products or services on the Internet, the perception of the safety of online shopping, as well as the main websites they have used in the last months.
Keywords: online shopping; e-commerce; internet; consumer